2021
DOI: 10.15311/selcukdentj.733453
|View full text |Cite
|
Sign up to set email alerts
|

Dental Ağrı Geçmişi Olan Hastaların Akılcı İlaç Kullanımına Yönelik Bilgi ve Davranışlarının Değerlendirilmesi

Abstract: Evaluation of Knowledge and Behavior of Ratinal Drug Use o Patients With Dental Pain HistoryBackground: Irrational use of drugs (IUD) is a common problem. In dentistry, which antibiotics, analgesics and some other drugs can be prescribed, there are problems with in the scope of IUD. In this study, it was aimed to investigate the habits and behavior in the use of drugs of individuals who applied to dental clinics due to dental pain.Methods: This study was conducted in the clinics of two different centers, the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…15 In a recent study on patients with a history of dental pain in Türkiye, 29.4% of the patients stated that they used medication for their dental problems without consulting a doctor. 20 Self-treatment without consulting a physician can lead to inadequate and incorrect treatment, suppression of symptoms and delay in early diagnosis of the disease, development of harmful drug and food interactions. When the results obtained from this study are compared with the results of previous studies in the literature, it shows that the participants are more conscious about consulting a doctor before drug use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 In a recent study on patients with a history of dental pain in Türkiye, 29.4% of the patients stated that they used medication for their dental problems without consulting a doctor. 20 Self-treatment without consulting a physician can lead to inadequate and incorrect treatment, suppression of symptoms and delay in early diagnosis of the disease, development of harmful drug and food interactions. When the results obtained from this study are compared with the results of previous studies in the literature, it shows that the participants are more conscious about consulting a doctor before drug use.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was determined that patients were more likely to comply with the recommendations of the physician and pharmacist in the use of drugs for dental reasons. 20 The most important reason for stopping using medication before the recommended time is that individuals believe they have recovered. 21 In Pechere's study with 5,379 participants from 9 countries, including Türkiye, 87% of the participants reported that they discontinued their medication if they felt better.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation